2016
DOI: 10.1212/wnl.0000000000003085
|View full text |Cite|
|
Sign up to set email alerts
|

Neurofilament light chain level is a weak risk factor for the development of MS

Abstract: Objective:To determine the prognostic value of selected biomarkers in clinically isolated syndromes (CIS) for conversion to multiple sclerosis (MS) and disability accrual.Methods:Data were acquired from 2 CIS cohorts. The screening phase evaluated patients developing clinically definite MS (CIS-CDMS) and patients who remained as CIS during a 2-year minimum follow-up (CIS-CIS). We determined levels of neurofascin, semaphorin 3A, fetuin A, glial fibrillary acidic protein, and neurofilament light (NfL) and heavy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
77
2
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(85 citation statements)
references
References 40 publications
5
77
2
1
Order By: Relevance
“…All of above might lead to overestimation of the test performance. It should also be noted that increased neurofilament level are not specific for ALS and have been reported in a number of other neurological diseases, including multiple sclerosis, dementia and brain trauma (Norgren et al, 2003; Skillback et al, 2014; Arrambide et al, 2016; Kirkcaldie and Collins, 2016; Xu et al, 2016). An ideal study should include other neurodegenerative disorders and ALS mimics as controls and use a pre-specified threshold.…”
Section: Discussionmentioning
confidence: 97%
“…All of above might lead to overestimation of the test performance. It should also be noted that increased neurofilament level are not specific for ALS and have been reported in a number of other neurological diseases, including multiple sclerosis, dementia and brain trauma (Norgren et al, 2003; Skillback et al, 2014; Arrambide et al, 2016; Kirkcaldie and Collins, 2016; Xu et al, 2016). An ideal study should include other neurodegenerative disorders and ALS mimics as controls and use a pre-specified threshold.…”
Section: Discussionmentioning
confidence: 97%
“…The CSF levels of NFL in patients with CIS have been reported to be an independent prognostic marker for conversion from CIS to MS [23][24][25], to correlate with MS severity score during long-term follow-up in MS [6] and to decrease on treatment [8]. To our knowledge, this is the first study to demonstrate that NFL at baseline is a strong predictor of disease activity in the comprehensive form of NEDA-3 status during 2 years of follow-up in CIS and newly diagnosed MS. We also confirmed that CSF levels of NFL predicted conversion from CIS to MS.…”
Section: Discussionmentioning
confidence: 99%
“…CSF NFL values were examined first. NFL is considered as a biomarker of axonal damage and is associated with conversion to MS in general CIS cohorts . In our ON series, CSF NFL levels seemed to be higher in patients who converted to CDMS, although differences were not significant.…”
Section: Discussionmentioning
confidence: 48%